Physiological and Nutritional Responses of Pear Seedlings to Nitrate Concentrations - Chen, Guodong; Wang, Li; Fabrice, Musana R.; Tian, Yanan; Qi, Kaijie; Chen, Qian; Cao, Peng; Wang, Peng; Zhang, Shaoling; Wu, Juyou; Tao, Shutian (Frontiers in Plant Science, 2018)
Nitrogen (N) is an important element for plant growth, and a suitable N supply is crucial to ensure optimal yields from fruit trees. Frequently, application of N fertilizers to fruit trees is often excessive, which not only leads to environmental pollution, but also reduces the output from fruit trees through N toxicity. To evaluate the effects of different concentrations of nitrate on plant growth, root-morphological traits, and other nutritional element’s responses in pear, pear seedlings (Pyrus betulifolia Bunge) were treated with five levels of N. Both N-deficiency and an excess of N inhibited the growth and development of pear rootstocks. However, different visible symptoms were observed among treated leaves and roots. Leaf yellowing, the stimulation of root elongation, a decrease in nitrate reductase activity and chlorophyll content were observed under N-deficiency conditions. On the other hand, dark green leaves accompanied by coking, the suppression of root elongation, and a decrease in nitrate reductase activity and chlorophyll content were displayed under regimes of excess N. In addition, not only the N content, but also the content of other mineral nutrients was influenced by nitrate treatments. Taken together, these results suggested that a careful choice of N fertilizer supply is crucial to ensure normal growth and development in pear trees.